Gas hydrate growth and dissociation in narrow pore networks: capillary inhibition and hysteresis phenomena - Anderson, Ross A.; Tohidi, Bahman; Webber, J. Beau W. (Geological Society, London, Special Publications, 2009)
Marine sediments hosting gas hydrates are commonly fine-grained (silts, muds, clays) with very narrow mean pore diameters (0.1 mm). This has led to speculation that capillary phenomena could play an important role in controlling hydrate distribution in the seafloor, and may be in part responsible for discrepancies between observed and predicted (from bulk phase equilibria) hydrate stability zone (HSZ) thicknesses. Numerous recent laboratory studies have confirmed a close relationship between hydrate inhibition and pore size, stability being reduced in narrow pores; however, to date the focus has been hydrate dissociation conditions in porous media, with capillary controls on the equally important process of hydrate growth being largely neglected. Here, we present experimental methane hydrate growth and dissociation conditions for synthetic mesoporous silicas over a range of pressure–temperature (PT) conditions (273– 293 K, to 20 MPa) and pore size distributions. Results demonstrate that hydrate formation and decomposition in narrow pore networks is characterized by a distinct hysteresis: solid growth occurs at significantly lower temperatures (or higher pressures) than dissociation. Hysteresis takes the form of repeatable, irreversible closed primary growth and dissociation PT loops, within which various characteristic secondary ‘scanning’ curve pathways may be followed. Similar behaviour has recently been observed for ice–water systems in porous media, and is characteristic of liquid–vapour transitions in mesoporous materials. The causes of such hysteresis are still not fully understood; our results suggest pore blocking during hydrate growth as a primary cause.